KOMPARASI HAFALAN AL-QUR’AN PESERTA DIDIK YANG TINGGAL DI PONDOK DAN LUAR PONDOK - Iwan Iwan (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2013)
The problem in this study is the difference in memorizing al-Qur'an of students who live in the cottage and outside the cottage. This type of research is quantitative. The population in this study amounted to 227 people and a sample of 80 people. Data collection tools using tests, interviews, observation and documentation. The previous test results were tested and tested for normality, tested for homogeneity and in the Mann Whitney test (Non-perametric Mean Difference). The results of this study are as follows: 1) The number of memorized al-Qur'an students who live in the cottage has a mean of 23.90 or about 24 surahs. 2) The number of memorized al-Qur'an students who live outside the cottage has a mean of 18.78 or about 19 surahs. 3) memorizing al-Qur'an of students who live in the cottage and outside the cottage, Z of -4.633 and Asymp. Sig. (2-tailed) 0,000, because of the Asymp. Sig. (2-tailed) = 0.000 <0.05 means that Ho is rejected and Ha is accepted. So that there is a significant difference in the number of memorized Al-Qur'an students who live in the cottage and outside the cottage, the number of memorized students who live in the cottage has a mean of 23.90 or about 24 chapters, while those who live outside the cottage have a mean of 18 , 78 or about 19 chapters. Thus, the difference in the number of memorized students who lived in the cottage and outside the cottage had a mean of 5.12 or about 5 surahs.